ANALISIS SELF EFFICACY DAN AKTIVITAS BELAJAR PESERTA DIDIK TERHADAP EFEKTIFITAS MODEL PEMBELAJARAN KNISLEY - Darsih Idayani; Lisma Dian Kartikasari (STKIP PGRI Situbondo, 2022)
This study aims to describe the condition of self-efficacy and student learning activities when the Knisley learning model is applied in the classroom. The approach used in this study is a qualitative descriptive approach assisted by percentage calculations. Data were collected by using observation, interviews, and questionnaires for class VII students at SMP Ainul Huda. From the findings, it can be known that the average self efficacy of learners for the category of high self efficacy levels was obtained by 23.3% and self efficacy with a moderate level category of 56.78%. Meanwhile, self-efficacy for the low-level category averaged 19.33%. Based on the results of observations and interviews, it is known that the learning activities of students which are divided into 4 main indicators are obtained that the 1st indicator of student learning activities is considered good, the second indicator of student learning activities is considered quite good, the 3rd indicator is considered quite good and student learning activities on the 4th indicator are considered very less. Based on the research findings, it can be concluded that the application of the Knisley learning model in mathematics learning is quite effective in increasing students' self-efficacy and learning activities but less effective in triggering students' learning activities to think creatively or reflectively (indicator 4).